Constructed Ag NW@Bi/Al core–shell nano-architectures for high-performance flexible and transparent energy storage device. Issue 37 (16th September 2020) - He, Xin; Liu, Junyan; Zhao, Sirou; Zhong, Yu; Chen, Bohua; Zhang, Chi; Yang, Weijia; Chen, Mei; Xin, Yue; Song, Mingxia; Cai, Guofa
Abstract : We developed an Ag NW@Bi/Al 1D hierarchical nanostructure as a negative electrode for flexible and transparent energy storage device (FTESD), which endows high transparency, improved energy/power density and electrochemical stability. Abstract : Flexible and transparent energy storage devices (FTESDs) have recently attracted much attention for use in wearable and portable electronics. Herein, we developed an Ag nanowire (NW) @Bi/Al nanostructure as a transparent negative electrode for FTESDs. In the core–shell nanoarchitecture, the Ag NW percolation network with excellent conductivity contributes superior electron transport pathways, while the unique nanostructure provides an effective interface contact between the current collector and electroactive material. As a result, the electrode delivers a high capacity of 12.36 mF cm −2 (3.43 μA h cm −2 ) at 0.2 mA cm −2 . With a minor addition of Al, the coulombic efficiency of the electrode remarkably increases from 65.1% to 83.9% and the capacity retention rate improves from 53.8% to 91.9% after 2000 cycles. Moreover, a maximum energy density of 319.5 μW h cm −2 and a power density of 27.5 mW cm −2 were realized by an interdigital structured device with a transmittance of 58% and a potential window of 1.6 V. This work provides a new negative electrode material for high-performance FTESDs in the next-generation integrated electronics market.